TLR2 Signaling Pathway Combats Streptococcus uberis Infection by Inducing Mitochondrial Reactive Oxygen Species Production - Bin Li; Zhixin Wan; Zhenglei Wang; Jiakun Zuo; Yuanyuan Xu; Xiangan Han; Vanhnaseng Phouthapane; Jinfeng Miao (Cells, 2020)
Mastitis caused by Streptococcus uberis (S. uberis) is a common and difficult-to-cure clinical disease in dairy cows. In this study, the role of Toll-like receptors (TLRs) and TLR-mediated signaling pathways in mastitis caused by S. uberis was investigated using mouse models and mammary epithelial cells (MECs). We used S. uberis to infect mammary glands of wild type, TLR2−/− and TLR4−/− mice and quantified the adaptor molecules in TLR signaling pathways, proinflammatory cytokines, tissue damage, and bacterial count. When compared with TLR4 deficiency, TLR2 deficiency induced more severe pathological changes through myeloid differentiation primary response 88 (MyD88)-mediated signaling pathways during S. uberis infection. In MECs, TLR2 detected S. uberis infection and induced mitochondrial reactive oxygen species (mROS) to assist host in controlling the secretion of inflammatory factors and the elimination of intracellular S. uberis. Our results demonstrated that TLR2-mediated mROS has a significant effect on S. uberis-induced host defense responses in mammary glands as well as in MECs.